Formulation and Evaluation of Lantana camara L. Leaf Extract Hair Tonic as an Anti-Dandruff and Hair Growth Agent - Nurul Husna; Sumaiyah Sumaiyah; Panal Sitorus (Indonesian Journal of Global Health Research, 2026)
Hair problems like loss and dandruff (Pityrosporum ovale) are common, fueling the search for natural alternatives. Lantana camara L. leaves, rich in flavonoids, saponins, and tannins, were selected for their antifungal and hair-growth promoting potential. This study formulated and evaluated a Lantana camara L. leaf ethanol extract hair tonic as an anti-dandruff agent (in vitro) and a hair growth promoter (in vivo). The extract was obtained via maceration and phytochemically screened. Hair tonic formulations (15%, 20%, 25%) underwent evaluation for physical stability, pH, viscosity, and microbial contamination, all meeting SNI standards. In vitro anti-dandruff tests against P. ovale used the disc diffusion method, while in vivo hair growth promotion was tested on mice for 30 days. Results confirmed the extract contained alkaloids, flavonoids, saponins, tannins, steroids, and triterpenoids. All formulas were stable and met SNI. The 25% formula (F3) showed superior microbial safety and strong in vitro antifungal activity (10.7 mm inhibition zone, comparable to positive control). In vivo, F3 significantly increased mouse hair length, comparable to commercial tonic by day 20. Flavonoids and saponins are suspected to contribute to hair growth stimulation. In conclusion, the Lantana camara L. leaf ethanol extract hair tonic 25% (F3) is safe, stable, effective as an anti-dandruff agent in vitro, and a hair growth promoter in vivo, positioning it as a promising natural alternative.